Attitudes, Perceptions, and Academic Performance: A Study of Computer-Based Examination Among Nursing Students in Osun State - Bakare, Olusegun Ojo; Bolarinwa, Adebola Arike (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The study determined the attitude and perception of nursing students towards computer-based examination in Osun State.  It also examined nursing students’ examination performances while using CBT and traditional methods. These were with a view to providing empirical information on the attitude and perception of student nurses towards the use of computer-based tests in Osun State. The study adopted a descriptive survey research design of the correlation type. The population for the study comprised all schools of nursing in Osun State. Out of this, six nursing schools were randomly selected using 20 nursing students from each school, totaling 120 respondents.  One instrument trial tested, yielding a Cronbach's alpha of 0.87, was used for the study. The data collected were analyzed descriptively and correlationally. The results revealed that the nursing students had a positive attitude towards the use of CBT. It further showed that the students demonstrated high perception towards the use of CBT in their exams.  There was a significant difference (p<0.05) between the average score obtained by the nursing students in CBT and the traditional method. The study concluded that the nursing students had a positive attitude and high perception towards the use of CBT and they preferred the CBT examination to the paper-based test.